Rossiia . Rossiia . Russia . Россия - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Journalist Dmitry Zakharov talks about current political events in Moscow. Contributors: Berezin, Vladimir (Anchor) Журналист Дмитрий Захаров высказывается по поводу текущих политических событий в Москве. Создатели: Березин, Владимир (Ведущий/Ведущая)